The global psychological and physical effects of domestic abuse and violence on South Asian women: a qualitative systematic review - Marina Masih; Christopher Wagstaff; Harjinder Kaur-Aujla (Frontiers Media S.A., 2024)
IntroductionThe purpose of this review is to systematically extract and analyse global academic literature to determine the physical and psychological effects of domestic abuse and violence on South Asian women.DesignThis review employs a qualitative systematic approach and thematic analysis to synthesize the narratives of affected women found in the literature. Given that domestic violence is often concealed and downplayed by various social factors, statistical reports and prevalence data offer only a limited view of the issue due to underreporting. Therefore, qualitative literature is deemed more dependable in this subjective domain as it captures and interprets the experiences and meanings within this under-studied group.Data sourcesEmbase, PsycINFO, Google Scholar, Web Of Science, MEDLINE, and ASSIA were searched.Review methodsAll included studies were critically appraised using the CASP tool for qualitative research. Thematic analysis was conducted to develop six themes. Studies excluded did not address the research question, although intersecting population issues could be valuable topics for further research.ResultsThe literature indicates severe mental and physical health consequences of domestic violence and abuse, with some traits persisting long-term. The analysis underscores the significant role of resilience, suggesting that individuals can overcome traumatic social experiences without enduring lifelong labels or a deficit model.ConclusionThe findings provide support for future interventions aimed at recognizing signs of abuse and preventing severe psychological and physical consequences, particularly among South Asian women. Further research is needed to understand the impact on children and other family members affected by the victim's abuse, which falls beyond the scope of this review.